The State of Continuing Qualitative Research on the Kennedy Assassination - Williams, John Delane (Journal of Scientific Exploration, 2023)
Followers of the Warren Commission’s findings continue to accept Lee Harvey Oswald as the assassin of President Kennedy. Deniers of the Warren Commission’s findings take a contrary view. Herein, the view is that Oswald had involvement with the assassination--- but that involvement was an attempt to stop the assassination. Oswald’s life is explored, focusing on his military service in Japan until his own death on November 24, 1963. Particular emphasis is placed on the writings Ernst Titovets (Oswald’s time in Russia); Judyth Baker (the summer of 1963 in New Orleans); Dick Russell’s writing of the experiences of Richard Case Nagell (in Atsugi Japan, 1957; and in Mexico City, New Orleans and El Paso, 1963); and Douglas Horne, on the medical evidence in the assassination. These writers correct the record of Oswald’s life. Baker shows Oswald’s continuing relations with Jack Ruby and David Ferrie, persons that were supposedly not known to Oswald. Baker clearly points out Oswald’s involvement in the project that aimed to eliminate Fidel Castro with a bio-weapon (a fast acting cancer). Russell shows the importance of Richard Case Nagell with Oswald. Horne elucidates the many missteps in the medical evidence in JFK’s autopsy. During Lyndon Johnson’s presidency (in 1965), a law was passed naming all materials involved in the JFK assassination were owned by the federal government. Christopher Fulton was the only person convicted under this statute, sentenced to 8 ½ years in prison, This occurred March 19, 1999.